FRI0378 National Audit of Vasculitis Inpatient Comorbidities and Mortality from 2005-14. (15th July 2016) - Harty, L.; Burns, S.; Jayne, D.
Abstract : Background: Incidence of inpatient (inpt) events, comorbidities and age of death for Irish vasculitis patients is currently unknown Objectives: Establish mortalitity & comorbidities in Irish vasculitis inpts Methods: The HIPE system was evaluated from 57 Irish hospitals between 2005–2014 for vasculitis inpt episodes (not individual patients) based on ICD10. Age, length of stay (LOS), gender and admitting indication and mortality were recorded. Results are shown as totals, % & median (IQR). The Mann–Whitney U test and χ 2 were employed Results: 5, 841 vasculitis inpt records were reviewed with median annual admissions of 601 (601–622). 2, 229 inpt admissions had large vessel vasculitis (LVV – Takayasu's & GCA) whose median age was 75yrs (66–81), LOS 6 days (3–13) and 68% were female. 3612 inpt admissions had small & medium vessel vasculitis (SMVV –GPA, eGPA, MPA, PAN, Behcet's, Goodpastures, Necrotizing & Juvenile Vasculitis) with a median age 58yrs (42–70), LOS 6 days (2–13) and 48% were female. MPA, eGPA and GPA admissions were more common for men whereas GCA, Takayasu's and Behcets admissions were more common for women ( table 1 ). 58% LVV inpts & 50% SMVV inpts were admitted for systemic inflammation (p<0.001). Infection was the next most common cause for admission (14% SMVV & 10% LVV, p<0.001). Ischaemic events were the 3rd most common reason for admission in LVV (7% v 3%, p<0.001) whereas renal failure was for SMVV (8% v 1%, p<0.001). Symptoms without a diagnosis were the 4th most common reason for admission (7% LVV & 5% SMVV, p=0.002). Figure 1 . Admission for cancer occurred in mean 2.5% and all other diagnoses accounted for <2% each. A greater percentage of SMVV inpts died than LVV inpts (4.1% v 2.7%, p=0.006) and they died younger (71yr (61–79) v 82 (76–86), p<0.001). Infection accounted for 28% of all deaths without difference between LVV and SMVV (p=0.5). More SMVV inpts died due to disease activity than LVV inpts (19% v 6%; p=0.03) and from renal failure (12% v 1%, p=0.05). More LVV inpts died from vascular infarction than SMVV (19% LVV v 6% SMVV; p<0.001). Male GPA inpts died younger than female (69yrs (62–78) v 79yrs (68–82); p=0.02). Conclusions: Around 600 vasculitis admissions occurred each year across the 57 hospitals directing the need for a concentrated number of centres of excellence to facilitate expert care, research and education. Small vessel vasculitis admissions were more common for men and large vessel and Behcet's for women. Despite advances in therapy systemic autoimmune disease and infection prevailed as causes for admission and death in vasculitis inpts, with greater mortality in SMVV from disease activity and renal failure and from vascular infarction in LVV. There is a need for improved diagnostic tests. Disclosure of Interest: None declared